S109 Contribution of aberrant monocyte-natural killer T (NKT) cell axis to immune-pathology in sarcoidosis. (2nd December 2011) - Crawshaw, A P; Kok, W L; Denney, L; Ho, L-P
Abstract : Introduction: Sarcoidosis is a multisystem disorder characterisedby an overactive CD4 (T-helper 1) cell response to an undefined antigen, macrophage activation and granuloma formation. It has also been shown that monocytes (precursors to macrophages) are increased in sarcoidosis. We have shown that NKT cells, a specialised subset of immuneregulatory T cells, are deficient in sarcoidosis, and that in NKT knock-out mice, monocytes accumulate at sites of inflammation in both models of influenza A infection and multiple sclerosis. Here, we hypothesise that NKT cells control monocyte function and that NKT cell deficiency in sarcoidosis results in abnormal monocyte activity. Methods: Twenty-five steroid-naïve non-smoking patients with histological confirmation of sarcoidosis were recruited from the Sarcoidosis-ILD service. Circulating monocyte numbers and phenotype were first characterised using multi-colour flow cytometry. We then isolated monocytes from blood using magnetic microbeads, examined cytokine production after LPS stimulation with intracellular cytokine FACS staining and ELISA; and using monocyte-NKT cell co-culture assays, questioned whether NKT cells affected these monocytic functions. Results: We found an increase in circulating CD14CD16 inflammatory monocytes in patients with sarcoidosis, and identified a population of interleukin 10 producing monocytes in patients and controls after LPS stimulation. Monocytes from sarcoidosis patients have reduced capacity to produce IL-10 after LPS stimulation compared to control (6.37% vs 11.71% of total monocytes, p<0.001, Abstract S109 figure 1A ); but addition of NKT cells improved this capacity (6.37% to 9.13%, p<0.001, Abstract S109 figure 1B ). We then questioned the role of IL10-producing monocytes and show (with mixed lymphocyte reaction and CFSE assays) that these cells suppress T cell proliferation (p<0.001, Abstract S109 figure 1C ). Conclusions: Our data show that sarcoidosis patients have increased inflammatory monocytes but a reduced IL-10-producing, T cell suppressing subset. NKTcells were able to interact with monocytes in vitro and increased IL-10 production by monocytes. These previously unrecognised findings, both in monocyte-NKT cross talk and in sarcoidosis immunobiology, suggest that one consequence of NKT deficiency in sarcoidosis is abnormal monocyte function with resultant loss in control of T cell proliferation. This reveals a potential new pathway of pathogenesis in sarcoidosis.